Sandiwara Sunda sebagai Bentuk Transmisi Nilai bagi Generasi Muda - Dwimarwati, Retno; Wita, Afri (PANGGUNG, 2013)
ABSTRACTÃÂ Character education is nowadays being promoted in national education system since it is consi- dered to be able to enhance the character of present and future generation. Character building cannot be separated from culture. In this case, Ringkang Gumiwang Arts House (RGAH) concerns on cha- racter education by reintroducing mother language (Sundanese) as an eÃ¯Â¬â¬ort to build oneÃ¢â¬â¢s culture. Reconstructing Sundanese play is conducted as an attempt of retaining the existence of Sundanese culture. The performance of Sundanese play grows into media of maintaining language and arts for young generation. Arts inheritance method is implemented to explore and apply the sustainment of arts in the society. Understanding of values in the performance is expected to be applied in the youth life. Therefore, the performance appreciation run by RGAH can be a model in transmitting values of a society. Plays (Sandiwara) become a good vehicle to increase appreciation among the youth.ÃÂ Keywords: Sundanese plays, values transmission, young generationÃÂ ÃÂ ABSTRAKÃÂ Pendidikan karakter kini tengah digalakkan dalam sistem pendidikan nasional karena dapat meningkatkan mutu karakter generasi sekarang dan masa datang. Kita tidak mung- kin membangun karakter terlepas dari budayanya. Padepokan Seni Ringkang Gumiwang (PSRG) peduli pada pendidikan karakter dengan mengenalkan kembali bahasa ibu(Sunda) sebagai upaya membangun budaya sendiri. Rekonstruksi Sandiwara Sunda dilakukan se- bagai upaya pemertahanan eksistensi budaya Sunda. Pertunjukan sandiwara Sunda men- jadi media pemertahanan bahasa dan seni kepada generasi muda. Metode Pewarisan kese- nian digunakan untuk menggali dan mengaplikasikan keberlangsungan sebuah kesenian di masyarakat. Pemahaman nilai-nilai yang terkandung di dalam pertunjukan diharapkan dapat diaplikasi dalam kehidupan siswa (generasi muda). Oleh karena itu, apresiasi per- tunjukan yang dilakukan oleh PSRG dapat menjadi model dalam transmisi nilai pada ma- syarakat. Sandiwara menjadi wahana tepat dalam peningkatan apresiasidi kalangan ge- nerasi muda.ÃÂ Kata kunci: Sandiwara Sunda, transmisi nilai, generasi mudaÃÂ